228k views
1 vote
4. (03.04)

Describe how to determine the average rate of change between x = 1 and x = 3 for the function f(x) = 3x³ +1. Include the average rate of change in your answer. (10 points)

User Greyfox
by
5.6k points

1 Answer

7 votes

Answer:

39

Explanation:

The given function to us is ,


\longrightarrow f(x) = 3x^3 + 1\\

We need to find the average rate of change between
x=1 and
x=3 .

We can calculate the average rate of change as ,


\longrightarrow A(x) =(f(b)-f(a))/(b-a)

So that ,


\longrightarrow A(x) =(f(3)-f(1))/(3-1)\\


\longrightarrow A(x) =\frac{ \{ 3(3)^3 +1 -(3(1)^3+1)\}}{2}\\


\longrightarrow A(x) = ( 81 +1 - 3 -1 )/(2)\\


\longrightarrow A(x) = (78)/(2)\\


\longrightarrow\underline{\boxed{ A(x) = 39}}

User Amy G
by
5.5k points